Impact of opening hermetic storage bags on grain quality, fungal growth and aflatoxin accumulation - Tubbs, Timothy (J Stored Prod Res, 2016)
Purdue Improved Crop Storage (PICS) bags are used by farmers in Sub-Saharan Africa for pest management of stored grains and products, including maize. These bags hermetically seal the products, preventing exchange with external moisture and gases. Biological respiration within the bags create an environment that is unsuitable for insect development and fungal growth. This study was conducted to determine the impact of routine opening of the storage bags for maize consumption on fungal growth and aflatoxin contamination. Maize with moisture contents (MC) high enough to support fungal growth (15%, 16%, 18% and 20%) was stored in PICS bags, which were opened weekly and exposed to humid conditions (85% RH) for 30 min over a period of 8 weeks and 24 weeks. Monitors indicated that oxygen defused into the open bags but did not reach equilibrium with the bottom layers of grain during the 30-min exposure period. Fungal colony forming units obtained from the grain surface increased 3-fold (at 15% MC) to 10,000-fold (at 20% MC) after 8 weeks. At both 8 weeks and 24 weeks, aflatoxin was detected in at least one bag at each grain moisture, suggesting that aflatoxin contamination spread from a planted source of A. flavus-colonized grain to non-inoculated grain. The results indicate that repeatedly breaking the hermetic seal of the PICS bags will increase fungal growth and the risk of aflatoxin contamination, especially in maize stored at high moisture content. This work also further demonstrates that maize should be properly dried prior to storage in PICS bags.